PRESERVATION OF ORGANIC MATTER AS AFFECTED BY VARIOUS CLAY CONTENTS IN AN ACID SOIL:BENEFICIAL IMPACT ON GROUNDNUT YIELD - ANDA, MARKUS; SURYANI, ERNA; KURNIA, UNDANG (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2008)
Systematic study on the effect of various clay contents on organic C dynamic and groundnut yield (Arachis hypogea) in upland acid soils has not received any attention. The objectives of the study were: (i) to assess the capability of various soil clay contents to preserve organic C, (ii) and to relate the effects of soil clay fraction and organic C on groundnut yield of an acid soil (Ultisol). The soil clay content was artificially adjusted to 15, 30, 45, 60 and 75%. Each soil clay percentage was thoroughly mixed with finely ground rice straw at the rate equals to 0.5, 1, 2, 3, 4, and 5% of organic C. The soil was then transferred into a pot and planted with corn (Zea mays)for the first 6 months and followed by groundnut for further 6 months. The experiment was arranged in a split plot design with three replications under glasshouse conditions. Results for the first 6 months have been published elsewhere. Hence, results for the last 6 months were presented here. Soil clay was the major factor responsible for the preservation of organic C as indicated by (i) the increased soil organic C with increasing clay fraction, and (ii) the low mineralization rate as shown by CO2-C: total C ratio from low to high 75<60<45<30<15% soil clay. It is observed that every 15% clay increment could preserve another 0.3% organic C for the period of 12 months. The increased soil organic C could linearly increase groundnut yield for 15 and 30% clay and quadratic yield for 45 and 60% clay. The maximum grain yield was 25.7-27.6 g pot-1 (equals to 2.9-3.1 t ha-1), which was obtained at 30-45 % clay containing 1.8-1.9% soil organic C.